IRRIGATION SCHEDULES AND PLANTING MODES impact ON FARMLAND MICROCLIMATE AND DRY MATTER ACCUMULATION OF WINTER WHEAT - X. B. Zhou; Y. X. Hu; G. Y. Wang; H. Y. Wu (Journal of Animal and Plant Sciences, 2020)
The economic yield of wheat (Triticum aestivum L) comes from the grain, and the dry matter accumulation of the grain is affected by the environmental factors, especially the temperature. A field experiment was conducted in Huanghuaihai Plain from 2014 to 2016 using thesplit-plot design with three replications following three irrigation schedules (main plot): irrigation of 50 mm each at jointing growth stage (GS34) and heading growth stage (GS48, W1); irrigation of 100 mm at GS48 (W2); and irrigation of 100 mm each at both GS34 and GS48 (W3) and three planting modes (split plot): uniform row (U), furrow (F), double-double row (DD) to explore the mechanism for improving yield and dry matter accumulation under reasonable temperature and relative humidity infarmland caused by irrigation and planting modes. The results showed that air temperature and relative humidity (RH) at 5 cm aboveground (AG5) were greater than those at 50 cm aboveground (AG50) during the two growing seasons. The average air temperature at AG5 and AG50 of W2 was 3.69% higher than that of W3, and RH was 5.21% lower than that of W3. With the increasing irrigation amount (W3) and frequency (W1), the average air and soil temperature were reduced while RH, dry matter accumulation rate for stem, leaf, spike and yield were increased significantly. Although DD and F as good planting modes have been detected to improve RH, dry matter and yield accumulation rates and decrease temperature as compared with U, the DD contributed more towards them. The AG5 and AG50 average air temperatures had a significantly negative correlation with total dry matter and yield accumulation rate, whereas RH showed the opposite mode. Meanwhile, spike dry matter accumulation rate plays a dominant role in improving yield because there was an extreme significant positive correlation between spike and yield accumulation rate. Consequently, irrigation 50 mm each at GS34 and GS48 combined with double-double row planting mode is a good agronomy method to be applied in the regions of scarce water resources like the Huanghuaihai Plain based on the water-saving technology.
Keywords: air temperature; dry matter; relative humidity; soil temperature; Triticum aestivum L